Endemic epigean Tenebrionids (Coleoptera: Tenebrionidae) from the Andean Region: exploring the patagonian-diversification hypothesis - Carrara, Rodolfo; Flores, Gustavo E. (Zootaxa, 2015)
Tenebrionidae is a diverse insect family of Coleoptera that shows high levels of endemicity in epigean species. For the Andean region, which is divided into three subregions: Central Chilean, Subantarctic and Patagonian, it has been hypothesized that epigean tenebrionids have diversified in the Patagonian subregion and subsequently, they dispersed to Subantarctic and Central Chilean subregions. In this work, based on information obtained from museum collections and scientific studies, we presented the first list of endemic epigean tenebrionids from the Andean region with their taxonomic arrangement and geographic distribution. Moreover, we used these data to explore the veracity of the Patagonian-diversification hypothesis. A total of 416 species grouped into six subfamilies, 17 tribes and 41 genera were identified as endemic to the Andean region. Considering the spatial distribution it was observed that subfamilies, tribes, genera and species were unequally distributed across subregions. Results did not support the Patagonian-diversification hypothesis; to the contrary, they were more concordant with processes of isolation among subregions that have promoted speciation by interrupting gene flow among populations, resulting in endemism because species can not expand their range sizes. Finally, we discuss the implications of our findings to be considered in biodiversity conservation, because endemic species, by their high extinction risk, are primary targets in conservation strategies.